2018
DOI: 10.1074/mcp.ra118.000698
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Proteomic Analysis of Pancreatic β-Cells in Response to Lipotoxicity and Glucolipotoxicity

Abstract: Chronic hyperlipidemia causes the dysfunction of pancreatic β-cells, such as apoptosis and impaired insulin secretion, which are aggravated in the presence of hyperglycemia. The underlying mechanisms, such as endoplasmic reticulum (ER) stress, oxidative stress and metabolic disorders, have been reported before; however, the time sequence of these molecular events is not fully understood. Here, using isobaric labeling-based mass spectrometry, we investigated the dynamic proteomes of INS-1 cells exposed to high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…As a member of methyltransferase family specifically targeting Histone H4 Lys20 for methylation, SETD8 plays an important role in cellular senescence, proliferation and apoptosis (59)(60)(61). Consistent with our results, multiple experiments indicated that changed expression level of SETD8 may affect insulinoma cell proliferation (62), hyperglycemic memory (63), and lipid metabolism (64). One study has shown that reducing the expression levels of SETD8 may contribute to altered hippocampal cellular composition, impaired neurodevelopment, and subsequent neurocognitive impairment (65), which are associated with the phenotype of SCZ.…”
Section: Discussionsupporting
confidence: 90%
“…As a member of methyltransferase family specifically targeting Histone H4 Lys20 for methylation, SETD8 plays an important role in cellular senescence, proliferation and apoptosis (59)(60)(61). Consistent with our results, multiple experiments indicated that changed expression level of SETD8 may affect insulinoma cell proliferation (62), hyperglycemic memory (63), and lipid metabolism (64). One study has shown that reducing the expression levels of SETD8 may contribute to altered hippocampal cellular composition, impaired neurodevelopment, and subsequent neurocognitive impairment (65), which are associated with the phenotype of SCZ.…”
Section: Discussionsupporting
confidence: 90%
“…Hyperglycemia could aggravate lipotoxicity-induced beta cell dysfunction (glucolipotoxicity) [5, 6]. Recently, transcriptomics and proteomics have been successfully adopted to discover major changes of protein-coding genes and proteins in pancreatic INS-1 cells exposed to glucolipotoxicity [18, 19]. Here, we revealed for the first time that the incubation of INS-1 cells with HG/PA caused considerable modifications in lncRNA expression.…”
Section: Discussionmentioning
confidence: 83%
“…INS-1 cells were grown to confluence, stimulated with 0.5 mM PA in the presence of 25 mM glucose (HG) for 24 h. The cell line and incubation conditions were chosen because 25 mM glucose/0.5 mM PA has been demonstrated to induce obvious glucolipotoxicity in INS-1 cells. Accordingly, this cell model has been used to explore the glucolipotoxicity-induced changes of mRNA microarray chips and proteomics [18, 19].…”
Section: Methodsmentioning
confidence: 99%
“…Other mass spectrometry methods have also been used to study beta cells. Recent temporal analysis of palmitic acid-treated INS-1 beta cells was based on isobaric labeling-based mass spectrometry and bioinformatics [64]. It highlighted altered cholesterol and fatty acid metabolism as early toxic events associated with ER stress.…”
Section: Lipidomic Analyses Of Beta Cellsmentioning
confidence: 99%